Relationship between pharyngeal response time and lateralized brain lesion in stroke - Alves, Thaís Coelho [UNESP]; Cola, Paula Cristina [UNESP]; Jorge, Adriana Gomes; Gatto, Ana Rita [UNESP]; Da Silva, Roberta Gonçalves [UNESP] (Taylor & Francis, 2019)
Objectives: To analyze the relationship between pharyngeal response time (PRT) and lateralization of brain lesions. Methods: A Cross-sectional study. 73 videofluoroscopic swallow studies (VFSS)were conducted on patients after stroke The study subjects were divided into : group 1 (G1) consisting of 39 individuals with left cortical lesion and group 2 (G2) consisting of 34 individuals with right cortical lesions. The VFSS of G1 and G2 subjects were analyzed using puree (A) and liquid (B) consistencies, and  were also subdivided into young adults and older persons. The mean PRT was divided into times shorter and longer than 250 ms. Results: No statistically significant difference was observed between G1 and G2 for the A and B consistencies, being obtained : G1 (A mean: 56.6 ms; B mean: 99.5 ms; A mean: 3627 ms; B mean: 1712 ms) and G2 (A mean: 79.6 ms; B mean: 110.7 ms; A mean: 2040 ms, B mean: 1529 ms), for PRT shorter (A:p =.673; B: p = 1.000) and longer (A: p =.435; B: p =.847) than 250 ms, respectively. No statistically significant difference was found regarding the variable age in the comparison between young and old adults for mean PRT according to the A and B consistencies in G1 (A: p =.260; B: p =.732) and G2 (A: p =.586; B: p =.104). Conclusion: No relationship between PRT and lateralization of brain lesion was observed with respect to subject age and to the swallowing of different food consistencies.
Keywords: deglutition disorder; quantitative analysis; software; stroke; Swallowing